Translation, cross-cultural adaptation and validation of the MBI-SS questionnaire for Chinese art students - Zhang Meng; Lay Yoon Fah (Humanities and Social Sciences Letters, 2024)
The 16-item Maslach Burnout Inventory-Student Survey (MBI-SS) was translated into simplified Chinese (MBI-SS-C) and tested for reliability and validity among Chinese art college students. A sample of 437 students from a Beijing art college was analyzed. The MBI-SS-C with 16 items shows relatively poor psychological measurement characteristics for items 2 and 7. The remaining 14 items showed good validity and reliability after being removed. Confirmatory factor analysis confirmed the structural validity of the 14-item MBI-SS-C. The Cronbach alpha for the MBI-SS-C was 0.854, with the three subscales having Cronbach alpha of 0.898, 0.890 and 0.902. The 14-item MBI-SS-C has a moderate correlation with general self-efficacy (GSE) and high concurrent validity. The 14-item MBI-SS-C is a reliable tool for evaluating burnout in Chinese art college students and is simple and effective.